PERSONAL DEVELOPMENT AND PROFESSIONAL FORMATION OF A STUDENT IN THE EDUCATIONAL INFORMATION ENVIRONMENT OF HIGHER EDUCATION INSTITUTIONS: A REFLEXIVE APPROACH - Luzik, Elvira; Semychenko, Valentyna; Selezen, Anna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article is devoted to considering the relevance of the problem of personal development and professional formation of a student as a subject of his life, who is able to critically analyze the state of the organization of the learning process and professional training in a higher education institution; determine directions for its optimization; to be aware of the degree of one's own activity in professional training; evaluate the relationship between teachers and students from the point of view of professional development expediency. The purpose of the article is to analyze global trends in personal growth and professional development of a student, which will justify the need to organize the educational process in a higher education institution on a student-centered basis. This made it necessary to carry out comprehensive research to identify, on a reflexive basis, the opinions of students regarding the scientific and methodological problems of organizing the educational process in higher education institutions; their involvement in identifying the main psychological and pedagogical problems in teaching; determination of prospects for the development of higher professional education. The results of the study confirmed the expediency of taking into account the identified socio-psychological factors and trends in society, which are accompanied by stress and conflicts. The statement that the effectiveness of off-line, on-line and mixed modes of the educational process in higher technical education can be significantly optimized, provided that the empirical material obtained in the research process is taken into account, is proven by the results of a pedagogical experiment in the appropriate educational information environment of the National Aviation University, which it is evidenced by the questionnaire conducted using multimedia technologies in the process of teaching courses of the cycle of professional training to future specialists. The conclusion made regarding the substantiation of the mechanism of taking into account the opinions of students regarding the scientific and methodological problems of organizing the educational process in higher education institutions will significantly increase the quality of teaching, the effectiveness of perception and assimilation of information by students